Calibration of traffic flow models using a memetic algorithm. (June 2015) - Paz, Alexander; Molano, Victor; Martinez, Ember; Gaviria, Carlos; Arteaga, Cristian
Highlights: The proposed methodology minimizes the time required by the analyst to setup a calibration model and get the desired results. Calibration of simulation-based traffic flow models using a Memetic Algorithm (MA). The proposed Memetic Algorithm (MA) is a combination of a genetic algorithm and a simulated annealing approach. Considering that the state-of-the-art uses simultaneous perturbation stochastic. Approximation algorithms, they are compared against and the proposed MA. The results illustrated the first highlight here. Abstract: A Memetic Algorithm (MA) for the calibration of microscopic traffic flow simulation models is proposed in this study. The proposed MA includes a combination of genetic and simulated annealing algorithms. The genetic algorithm performs the exploration of the search space and identifies a zone where a possible global solution could be located. After this zone has been found, the simulated annealing algorithm refines the search and locates an optimal set of parameters within that zone. The design and implementation of this methodology seeks to enable the generalized calibration of microscopic traffic flow models. Two different Corridor Simulation (CORSIM) vehicular traffic systems were calibrated for this study. All parameters after the calibration were within reasonable boundaries. The calibration methodology was developed independently of the characteristics of the traffic flow models. Hence, it is easily used for the calibration of any other model. The proposed methodology has the capability to calibrate all model parameters, considering multiple performance measures and time periods simultaneously. A comparison between the proposed MA and the Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm was provided; results were similar between the two. However, the effort required to fine-tune the MA was considerably smaller when compared to the SPSA. The running time of the MA-based calibration was larger when it was compared to the SPSA running time. The MA still required some knowledge of the model in order to set adequate optimization parameters. The perturbation of the parameters during the mutation process must have been large enough to create a measurable change in the objective function, but not too large to avoid noisy measurements.